Peatland degradation level and restoration model of Perigi Village in Ogan Komering Ilir, South Sumatra, Indonesia - Bakri, Bakri; Imanudin, Momon Sodik Imanudin; Napoleon, A; Syazili, As’ad Syazili; Prayitno, Muh Bambang Prayitno; Hermawan, A.; Khoiriyah, Z; Suwignyo, Rujito A; Choi , Eunho; Yang, Hyunyoung (Brawijaya University, 2025)
The use of peatlands for plantations and industrial tree plantations is increasingly widespread and causes land degradation due to excessive drainage. Meanwhile, adaptive agricultural efforts are not yet appropriate for maintaining the peatland environment. This study aimed to assess peatland degradation in Perigi Village, Pangkalan Lampam District, Ogan Komering Ilir Regency. Data obtained were analyzed using a descriptive method, followed by an evaluation of the determination of the level of land degradation with standard criteria for land degradation in wetlands based on the Regulation of the Indonesian Minister of Environment No. 20, 2008. The observations, field measurements, and laboratory analysis showed that the three lands experienced moderate degradation. The parameters that limit and contribute to the land degradation score to a moderately degraded status are shallow groundwater depth, redox, and soil pH that exceeded the threshold value. Adaptive technology must accommodate local knowledge and can increase farmer income.